Advancing the quality of environmental microplastic research. (24th May 2017) - Connors, Kristin A.; Dyer, Scott D.; Belanger, Scott E.
Abstract: Investigations into the environmental fate and effects of microplastics have been gaining momentum. Small, insoluble polymeric particles are implicated by scientists in a wide variety of studies that are used to suggest a potential for widespread impacts in freshwater and marine pelagic and sediment environments. An exponential growth in scientific publications and an increase in regulatory attention have occurred. However, despite these efforts, the environmental hazard of these particles is still unknown. To evaluate the hazard of microplastics within a risk assessment context, we need a way to evaluate the quality of experimental studies. We performed a thorough review of the quality and focus of environmental microplastic research, to understand the methodologies employed and how this may assist or distract from the ability of environmental risk assessors to evaluate microplastics. We provide guidance to improve the reliability and relevance of ecotoxicological studies for regulatory and broader environmental assessments. Nine areas of needed improvement are identified and discussed. Important data gaps and experimental limitations are highlighted. Environ Toxicol Chem 2017;36:1697–1703. © 2017 SETAC